Regulation of TNF-α and NF-κB activation through the JAK/STAT signaling pathway downstream of histamine 4 receptor in a rat model of LPS-induced joint inflammation. - Ahmad, Sheikh Fayaz; Ahmad Ansari, Mushtaq; Zoheir, Khairy M.A.; A.Bakheet, Saleh; M.Korashy, Hesham; Nadeem, Ahmed; Ashour, Abdelkader Elbadawy Abbas; Attia, Sabry M. (Elsevier, 2015)
Histamine 4 receptor (H4R) is a novel target for the pharmacological modulation of histamine-mediated immune signals during inflammatory diseases. The purpose of this study was to assess the effects of the H4R agonist 4-methylhistamine dihydrochloride (4-MeH) and antagonist JNJ7777120 (JNJ) in the inflamed rat knee. Animals were fasted for 18h before a single dose of 4-MeH or JNJ (30mg/kg) was administered intraperitoneally (i.p.), both followed by intra-articular (i.a.) injection of LPS 2h later. Blood and synovial fluid were collected after a short incubation period and TNF-α, NF-κB, and IkB-α levels were measured via flow cytometry. Additionally, we assessed the effects of H4R engagement on the expression of IL-1β, TNF-α, and NF-κB mRNAs and the protein levels of TNF-α, NF-κB, JAK-1, and STAT-3 in the inflamed knee tissue. These results revealed increased TNF-α and NF-κB expression and decreased IkB-α levels in both the LPS alone and 4-MeH treated groups in whole blood and synovial fluid. Further, IL-1β, TNF-α, and NF-κB mRNA levels were significantly increased and western blot analysis confirmed increased expression of TNF-α, NF-κB, JAK-1, and STAT-3 in both LPS and 4-MeH treatment groups. Furthermore, these increases were completely inhibited in the inflamed knee tissue of the JNJ-treated group. Thus, the inhibition of inflammatory mediators and signaling pathways by the H4R antagonist JNJ suggests the anti-arthritic importance of this molecule.